Optimization of spray dried yogurt and its application to prepare functional cookies - Ali, Anwar; Javaid, Muhammad Tasawar; Tazeddinova, Diana; Khan, Ahmal; Mehany, Taha; Djabarovich, Toshev Abduvali; Siddique, Rabia; Khalid, Waseem; Tariq, Tayyaba; Lai, Wing-Fu (Frontiers in Nutrition, 2023)
The present study aims to optimize the spray dried yogurt conditions, as well as to evaluate the effect of incorporation of spray dried yogurt at several ratios on the developed functional cookies charcterstics in term of physicochemical, baking qualities, bioactive profile, and sensorial aspects. Yogurt was spray dried by employing different outlet air temperatures (OAT) (65°C, 70°C & 75°C) and inlet air temperatures (IAT) (150°C, 155°C & 160°C). Spray drying shows that increasing the temperature increases nutritional loss, whereas S. thermophilus culture resists intensive heat approaches. On the other hand, L. delbrueckii subsp. bulgaricus culture was found to be significantly affected. A total of 4 treatments, including one control for the functional cookies development. A directly proportional relation was investigated between the increasing concentration of SDYP and baking characteristics and the cookie's mineral and protein profile. Bioactive parameters like antioxidant activity of 2, 2-diphenyl-1-picryl-hydrazine-hydrate (DPPH), 2, 2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), and total phenolic content (TPC) were also affected significantly. The sensory profile shows an incline towards T0 (0% SDYP) to T3 (10% SDYP) in all attributes but starts to decline when the concentration of SDYP reaches 15%. This study suggests that by employing a certain combination of temperatures (OAT: 60°C IAT: 150°C), maximum survival of inoculated culture can be achieved, and this powder can be utilized in the development of functional cookies that can be developed with enhanced sensory as well as biochemical characteristics at level (P< 0.05).